(untitled) (Research, Society and Development, 2024)
The objective of the present work was to evaluate the impact of intermittent fasting on people with type 2 diabetes. The type of study addressed is a integrative review, which analyzes the results presented in human case studies collected in the PubMED, Googledocs databases, Ebsco, among others. The following descriptors were used: intermittent fasting, diabetes, obesity, intermittent fasting in diabetes, intermittent fasting, diabetes, obesity, intermittent fasting in diabetes. Articles published in the last 10 years were included and around 23 references were consulted. Intermittent fasting (IF) has been shown to be beneficial in the treatment of type 2 diabetes, resulting in reduced body weight, improved glycemic control and possibly improved disease control. Although studies are limited, there is preliminary evidence suggesting benefits in reducing weight and improving blood glucose levels. However, long-term studies are needed to fully evaluate the benefits and risks of this approach.